2022
DOI: 10.1039/d2cc05218k
|View full text |Cite
|
Sign up to set email alerts
|

Absolute configuration determination of SMTP-7 via microcrystal electron diffraction (MicroED)

Abstract: The absolute configuration of a clinically important drug candidate, SMTP-7, with only micron-sized powders available, is directly obtained via microcrystal electron diffraction (MicroED) analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We also suggested that 3D ED/MicroED could be applicable to directly determine the absolute configuration of natural products by the previously reported method. 2,3 3D ED/MicroED is currently attracting attention as a method for structure determination of small molecules. 1,22–26 To the best of our knowledge, this is the first time that the absolute configuration of natural compounds is directly elucidated by 3D ED/MicroED and confirmed by derivatization and SCXRD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also suggested that 3D ED/MicroED could be applicable to directly determine the absolute configuration of natural products by the previously reported method. 2,3 3D ED/MicroED is currently attracting attention as a method for structure determination of small molecules. 1,22–26 To the best of our knowledge, this is the first time that the absolute configuration of natural compounds is directly elucidated by 3D ED/MicroED and confirmed by derivatization and SCXRD.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, it is still necessary to verify whether 3D ED/MicroED can be utilized to directly determine the absolute configuration of organic molecules including natural products, unlike SCXRD, although computational tools of dynamical refinement on 3D ED/MicroED data have been recently developed. 2,3 Fungal infections cause more than 150 million cases of severe diseases worldwide and about 1.7 million deaths annually. 4 Among them, aspergillosis and candidiasis are the frequently reported opportunistic mycoses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the research of Hasumi et al, , SMTP-7 is made by a fungal fermentation process that generates Pri-SMTP in situ , which is oxidized to the dialdehyde intermediate Pre-SMTP followed by a condensation reaction with l -ornithine (Scheme ). The stereoconfigurations of C-2 and C-3 in the pyran ring were originally assigned as (2 S ,3 S ) and later corrected to be (2 R ,3 S ) from a single-crystal X-ray analysis of a similar SMTP-derived compound. , However, to date, there has not been unambiguous proof of the absolute stereochemistry of SMTP-7, itself . To prove its structure unambiguously, its total synthesis was undertaken.…”
mentioning
confidence: 99%